Kuartet Biologi Digital Application to Build Digital Literacy and Cognitive Learning Outcomes of Students in High School - Sari, Debby Trisia; Susilo, Herawati; Balqis, Balqis (BIOEDUKASI, 2024)
Digital literacy is understood as a person's way of thinking, attitude and skills in using electronic and digital devices appropriately to help with work. One of the efforts to integrate digital technology into learning is by using learning applications, namely the Kuartet Biologi application. This research focuses on building students' digital literacy and cognitive learning outcomes through the Kuartet Biologi application. This study involved 58 students of class XI IPA SMAS Elim Makassar, South Sulawesi using a pre-test-post-test design with a non-equivalent control group. The pretest score as a covariant to analyse students' cognitive learning outcomes. Digital literacy was done by observation from the observer as many as 15 statements. Digital literacy was analysed using ANOVA test. Cognitive learning outcomes were analysed using ANCOVA test. The results showed the effect of digital literacy is 0.00 < 0.05 and cognitive learning outcomes of students who used the Biology Quartet application with classes did not use it is 0.00 < 0.05. The Kuartet Biologi application is proven to be more effective in building digital literacy and cognitive learning outcomes of students to build cognitive, technical, social-emotional, and behavioural dimensions in using electronic devices while learning and helping students have better knowledge.